Discovery of therapeutic targets in cardiovascular diseases using high-throughput chromosome conformation capture (Hi-C) - Quan Zheng; Ying Liu; Ying Liu; Minghao Guo; Xin Zhang; Qingbin Zhang; Xi-Yong Yu; Zhongxiao Lin (Frontiers in Genetics)
Epigenetic changes have been associated with several cardiovascular diseases. In recent years, epigenetic inheritance based on spatial changes has gradually attracted attention. Alterations in three-dimensional chromatin structures have been shown to regulate gene expression and influence disease onset and progression. High-throughput Chromosome Conformation Capture (Hi-C) is a powerful method to detect spatial chromatin conformation changes. Since its development, Hi-C technology has been widely adopted for discovering novel therapeutic targets in cardiovascular research. In this review, we summarize key targets identified by Hi-C in cardiovascular diseases and discuss their potential implications for epigenetic therapy.